THE ENTREPRENEUR PROGRAM IN EARLY CHILDHOOD EDUCATION INSTITUTIONS: A CASE STUDY OF MARKET DAY - Pratiwi, Eriqa; Latif, Muhammad Abdul; Fatihatus Sholihah, Yesi Ardana (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Entrepreneurship is an effective strategy for reducing unemployment in Indonesia, which is currently experiencing an increase in the unemployment rate. This issue poses a significant challenge to the country’s economic development. This study aims to uncover entrepreneurial innovations from an early age as a foundation for children to face increasingly competitive markets. The method used in this research is qualitative with a case study approach. Data collection was carried out through observations, interviews, and documentation. The sources of data include literature, scientific articles, as well as information from the principal and teachers at Muslimat NU Darunnajah Kindergarten in Kamal. The results of the study show that the entrepreneurial innovation program in early childhood education includes activities such as market day, art exhibitions, and educational tourism. These activities are designed to train children to have an entrepreneurial spirit from an early age, where they learn to take risks and think critically. This program not only provides practical experience but also helps children develop essential social and emotional skills. By instilling an entrepreneurial spirit, children are expected to be better prepared to face future challenges. Therefore, this research contributes significantly as one of the ways to prepare future generations for a competitive world. Through entrepreneurship education, children not only learn about business but also about values such as teamwork, creativity, and perseverance, which are crucial for building their character. Thus, entrepreneurial innovation in early childhood education can be one of the solutions to address the unemployment issue in Indonesia in the future.